DAMPAK PELAKSANAAN PERATURAN DAERAH TERHADAP PEMAKAIAN BUSANA MUSLIM DI KECAMATAN PADANGSIDIMPUAN TENGGARA - Ajim Harahap, Zul Anwar (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
This research begins with an initial hypothesis that there is a positive impact on the issuance of regional regulations regarding the obligation to wear Muslim clothing in the city of Padangsidimpuan. This research was conducted in a sub-district in Padangsidmpuan City, South Padangsidimpuan Subdistrict, as an instrument for data collection carried out by direct observation. The results obtained from the observation and dissemination of the questionnaire obtained that the public's knowledge of the obligation to wear Muslim clothing showed that most people knew it. (an average of more than 80%) Public knowledge about the issuance of local regulations governing the obligation to w.